MODEL OF SEISMIC VELOCITY DISTRIBUTION FOR COMPLETE COMPLEX OF PROCESSING AND INTERPRETATION OF SEISMIC DATA IN DNIEPER-DONETS BASIN - Petruniak, V.; Ustenko, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Advanced understanding of geological structure of petroleum fields remains one of the main drivers of successful exploration and production. Due to limitations of seismic method we can acquire data only in time domain, while other data, like petrophysical or geological, are acquired in depth. Combining these main data sources in a single exploration project remains one of the main task of exploration geologist since it allows avoiding mistakes in depth estimation of prospects, and thus correct estimations for drilling. The key for correlations between time and depth domain is vertical seismic profiling (VSP), which allows estimation of seismic waves' travel time with depth. Basically, so far this is the only direct measurement of time-depth relationship in petroleum fields. Correct processing and interpretation of this data will lead to correct interpretation and prospect evaluation. In the paper VSP data processing workflow is being proposed. Calculation methods of interval, average and layer velocities and statistical methods to crosscheck obtained results are suggested. Statistical analysis allows avoiding subjective mistakes, and though in some situations might require later manual corrections for geological factors, nevertheless it allows to guarantee quality of the data and introduces unique approach to its interpretation. Obtained seismic velocities later were incorporated in seismic data processing graph and an optimal graph for processing seismic data using VSP velocities is introduced. Applying well velocity data allows us to properly estimate velocity models for depth migration and to avoid uncertainties related to velocity estimation. Seismic images, obtained after processing, were used for seismic interpretation, which helped to specify geological structure of the prospects in the cutoff part of the Dnieper-Donets Basin. Modern software and interpretation methods of seismic data allow significant improving of mapping accuracy and tracing tectonic faults.